2003
DOI: 10.1364/ol.28.000610
|View full text |Cite
|
Sign up to set email alerts
|

Directionality of Gaussian Schell-model beams propagating in atmospheric turbulence

Abstract: It is known that some partially coherent Gaussian Shell-model beams may generate, in free space, the same angular distribution of radiant intensity as a fully coherent laser beam. We show that this result also holds even if the beams propagate in atmospheric turbulence, irrespective of the particular model of turbulence used. The result is illustrated by an example.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(51 citation statements)
references
References 5 publications
2
43
0
1
Order By: Relevance
“…Therefore the total log intensity due to large-scale and small-scale is (12) 4 Result and discussion Fig. 2 shows the degradation of scintillation index when using the diffuser for strong turbulence.…”
Section: Log Intensitymentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore the total log intensity due to large-scale and small-scale is (12) 4 Result and discussion Fig. 2 shows the degradation of scintillation index when using the diffuser for strong turbulence.…”
Section: Log Intensitymentioning
confidence: 98%
“…Recently, phase screen diffuser which generates partial coherent beam has rising interest especially to improve the performance in laser communication system [10][11][12][13]. The original FSO employs the perfect coherence beam suffers some problems depends on weather condition.…”
Section: Introductionmentioning
confidence: 99%
“…(14) in [54] because of a quadratic approximation of Rytov's phase structure function is used; i.e., z 6/5 appears in the second term of Eq. (19) here, while z occurs in [54]. Eq.…”
Section: Mean-squared Beam Width and Angular Spread Of Partially Cohementioning
confidence: 99%
“…It has been widely recognized that partially coherent laser beams are less affected by turbulence than their coherent counterparts [7,18,24,29,32]. It is also indicated that the use of higher-order model source can also reduce this degradation [3,27,28].…”
Section: Introductionmentioning
confidence: 99%